The Role Of The Muhammadiyah Preachers Corps In The Development Of Islamic Da'wah Education In The Blimbing Branch - Himma Nabila; Mohammad Zakki Azani (Green Publisher Indonesia, 2025)
This research was conducted to obtain data or information related to the Muhammadiyah Missionary Corps Blimbing Branch. The purpose of this research is to find out the development of Islamic da'wah education in the Blimbing Branch with the existence of the Muhammadiyah Missionary Corps and to find out the supporting and inhibiting factors of Islamic da'wah in the area. This type of research is qualitative descriptive research. The data sources obtained for this study consisted of two categories, the first was primary data sources derived from observations and interview results, the second was secondary data sources derived from manuscripts, documents, and information related to the Muhammadiyah Blimbing Missionary Corps. The results of this study are: The Blimbing Branch of the Muhammadiyah Missionary Corps has a very significant role in the process of deepening, practicing and appreciating Islamic da'wah in the Blimbing Branch area and its surroundings. The supporting factors for the running of KMM da'wah are: solid leadership, adequate facilities, crowded missionaries in the Blimbing Branch, and financial support from the Muhammadiyah Tabligh Council.